International Experience of Organizing Cooperation between police and Public (Law and Safety, 2020)
International experience of the interaction between the police and the public within law enforcement activity has been analyzed. The urgency of scientific research on the problems of establishing effective interaction between representatives of public organizations and employees of the National Police has been emphasized. In order to increase the effectiveness of public participation in the protection of public order and the fight against offenses in our country, the author has analyzed international experience of both individual citizens and public law enforcement organizations in general. Citizens’ participation in the fight against crime is a fundamental condition, because it was not possible to construct an effective system of influencing crime without the support of the population in any country. The strategy, which envisages cooperation between the population and police officers in the field of combating crime in the EU countries, complements police practice. Cooperation of public associations with the police ensures the achievement of more effective results in the field of law enforcement activities.It has been concluded that the effectiveness of public order protection and the fight against crimes is possible only in case of the participation of the wide range of population. It has been offered to borrow the programs of foreign colleagues and gradually introduce the model of policing based on the consent of the population, the use of which can improve the rule of law and fight against offenses in Ukraine.It has been proved that the considered programs of interaction of police of foreign countries with the population can be used in the activities of the National Police of Ukraine that can promote the increase of the level of keeping public order and safety both in the state in the whole, and in each administrative and territorial unit. Due to the use of international experience in involving citizens in the protection of public order, it will be able to focus law enforcement activities on long-term service to society in order to ensure its security.
Keywords: international experience; public order and security; protection; police; public associations; interaction; forms